Demand and Supply Side Linkages in Exporting Multiproduct Firms - Carsten Eckel; Lisandra Flach; Ning Meng (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2023)
Products produced by a multiproduct firm can be linked through demand linkages or supply linkages. On the demand side, changes in the price of one product can affect the demand for a firm's other products through shifts in consumer expenditures. This is commonly referred to as the cannibalization effect. On the supply side, joint inputs can create a dependency of one product's marginal costs on the output of other products. The existence of these linkages is important for how firms respond to shocks and has major implications for several performance measures, such as productivity and markups. This paper provides first empirical evidence for the existence of cannibalization linkages in presence of supply linkages, which is implied evidence for market power.
Keywords: D21; D24; F12; F13; F14; L11; L15; L25; 330; multiproduct firms; cannibalization effect; demand linkages; supply linkages; anti-dumping tariffs; quality; mark-ups